2021
DOI: 10.1177/10659129211009605
|View full text |Cite
|
Sign up to set email alerts
|

What Satisfaction with Democracy? A Global Analysis of “Satisfaction with Democracy” Measures

Abstract: Asking citizens “the way democracy works” is the basis of a wide literature on the support citizens have for their political institutions and is one of the most common survey items in political science. Moreover, it is a key indicator for the purported global decline in legitimacy. Yet, its trends, levels, and dynamics are still debated, and conclusions may be erroneous. In this paper, we compile a unique global dataset between 1973 and 2018 encompassing all major cross-national datasets and national election … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…We agree with recent interventions that argue SWD should be interpreted as measuring a concept between these two extremes (Valgarðsson and Devine, 2022; Norris, 2011). In mature democracies, SWD is not a measure of preference for democracy as against other forms of government, since in nearly all these countries over 90 per cent of citizens think that democracy is best, yet aggregate SWD varies from about 40 per cent to 90 per cent.…”
Section: How Satisfying Is Satisfaction Research?supporting
confidence: 90%
“…We agree with recent interventions that argue SWD should be interpreted as measuring a concept between these two extremes (Valgarðsson and Devine, 2022; Norris, 2011). In mature democracies, SWD is not a measure of preference for democracy as against other forms of government, since in nearly all these countries over 90 per cent of citizens think that democracy is best, yet aggregate SWD varies from about 40 per cent to 90 per cent.…”
Section: How Satisfying Is Satisfaction Research?supporting
confidence: 90%
“…Rescaled averages of responses to the trust question with the 10-point scale in EB tend to be lower (and close to means from the 10-point EQLS scale) than those from the usual binary scale. For a more thorough analysis of scale and project effect with regard to political support, see, for example, Valgarðsson and Devine (2021).…”
Section: Illustration: Trust In Institutionsmentioning
confidence: 99%
“…One such challenge emerges in the harmonization of ordinal rating scales of different lengths, as in the trust example, where different mapping approaches are possible. In one approach, the target scheme would be the simplest one, that is, a binary scale, and longer response scales in the source data are dichotomized (the midpoints in scales with odd number of points can be either collapsed with one of the two target categories, or discarded as missing data; for an example of the latter application see Valgarðsson and Devine, 2021). Another approach involves rescaling to a common range while keeping all the interim values.…”
Section: Limitationsmentioning
confidence: 99%
“…While increasing trust in implementing institutions is likely to be generally considered a positive development (seeTyler 2001), it seems to us worrisome from a democratic perspective that citizens are growing more trusting of non-representative institutions at the same time as they have grown less trusting of representative institutions, as this might pave the way for nondemocratic political leaders to use the state in more autocratic ways. Other studies have demonstrated that people's support for democratic ideals(Claassen 2019b;Dalton 2004;Stoker 2017) and their 'satisfaction with the way democracy works'(Claassen and Magalhães 2022;Valgarðsson and Devine 2021) remain steady at high levels, but eroding trust in the institutional mechanisms intended to bring democracy about may nevertheless directly or indirectly threaten the future of democratic governance (e.g Easton 1965;Hetherington 2005)…”
mentioning
confidence: 99%